Readability Analysis Of Physics Module Based On PBL For Vector And Newton Laws Material For X Grade Students In Senior High School - Nurul Fitria; Ananda Regina Berlian; Rahmatul Ula Asshaumi; Lady Pretylia Iraynida Disha; Rahma Dwi Febryani; Achmad Sulaimanul Hakim; Mila Nurfaniyah; Moh. Kelvin Rikza Aziizi; I Ketut Mahardika; Subiki Subiki (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Language validation aims to determine the accuracy of the use of language in the module. It is intended that the information to be conveyed by the module can be conveyed clearly to the reader. This research was conducted to determine the language validity of the PBL (Problem Based Learning) physics module on vector material to find out how appropriate it was for X grade students in high school. The method used in this research was a qualitative descriptive research method. By using a research procedure that was calculating the validation results obtained, then providing the criteria and categories of the percentage of the results of the assessment of the validity value. From the results of this study, the overall value of language validation was obtained, namely 81.25% with a very decent category.